ANALISIS PENDAPATAN USAHA PETERNAK SAPI POTONG DI KECAMATAN WEDA SELATAN KABUPATEN HALMAHERA TENGAH - Aiba, Aksen; Loing, J C; Rorimpandey, B; Kalangi, L S (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ INCOME ANALYSIS OF SMALLHOLDER FARMERS FOR BEEF CATTLE IN SOUTH WEDA DISTRICT OF CENTRAL HALMAHERA REGENCY. Objective of this study was to evaluate the income and factors affecting income of smallholder farmer of beef cattle on the high land and low land at South Weda district of Central Halmahera regency. Samples of these smallholder farmers were defined by purposive method based on high population of beef cattle. Quantitative data were analyzed by multiple regression model. Results showed that the average production costs were IDR 37,310,606.00 on high land location and IDR 25,597,372.00 on low land location. The average output of smallholder farmers from beef cattle were IDR 56,397,059.00 on high land location and IDR 38,475,000.00 on low land location. Therefore, their incomes were IDR 19,086,453.00/year on high land location and IDR 12,877,628.00/year on low land location. Result of multiple regression analysis showed that beef cattle stock variable (animal value at end of year) affected on the smallholder farmer income of beef cattle, while education and age of smallholders did not affect on their income at South Weda district of Central Halmahera regency.Â Key words: Smallholder farmer income, South Weda district Central Halmahera regency.